Influence of Recycled Plastic Incorporation as Coarse Aggregates on Concrete Properties - Ali, Khawar; Saingam, Panumas; Qureshi, Muhammad Irshad; Saleem, Shahzad; Nawaz, Adnan; Mehmood, Tahir; Maqsoom, Ahsen; Malik, Muhammad Waqas; Suparp, Suniti (My University, 2023)
Plastic waste has increased significantly in recent years as a result of fast population growth and urbanization. Studies on the incorporation of plastic aggregates as a substitution for natural aggregates in concrete are needed to successfully reduce both adverse environmental impact and the depletion of natural resources. The objective of this research was to investigate the use of plastic as a partial substitution for natural coarse aggregates in concrete. For this purpose, seven concrete mixes were produced using 0, 10, 15, and 20% plastic coarse aggregates to replace natural aggregates with and without silica fume of similar replacement levels with cement. Fresh density, workability, compressive strength, splitting tensile strength, stress–strain response, and Poisson’s ratio were observed to study the fresh as well as hardened properties of concrete mixtures. Indoor and outdoor thermal performance and thermo-gravimetric analysis were also investigated. The results revealed that the plastic aggregates’ incorporation improved the workability of concrete; however, it negatively influenced the fresh density and mechanical properties of concrete. The compressive and tensile strengths of plastic aggregate concrete without silica fume were reduced by 32 and 33%, respectively. The reduction in strength could be associated with the smooth texture of plastic aggregates. The addition of silica fume with plastic aggregates resulted in denser concrete and improved mechanical properties. In general, the performance of plastic aggregates as a partial replacement for natural aggregates was satisfactory, which suggests their possible use to produce eco-friendlier concrete.
Keywords: plastic waste; recycling; silica fume; stress–strain behavior; sustainability; thermal performance